Development of MojiGoiGo!: Adobe Flash Based Learning Media For JLPT Preparation - Krishna Adnyani, Kadek Eva; Satya Hermawan, Gede; Partha Sindu, I Gede (Universitas Pendidikan Ganesha, 2018)
This study aims to develop Adobe Flash CS6